Purchasing and supply chain management : a sustainability perspective - Johnsen, Thomas E.; Howard, Mickey, 1967-; Miemczyk, Joe (Routledge, Taylor & Francis Group, 2014)
"Supply chain management is a cross-functional business concept that includes, for example, logistics and operations management. In many organizations purchasing is now part of the supply chain management function. In addition, the age of the "triple bottom line" is upon us: the issue of sustainability seems certain to gain great momentum and a company is no more sustainable than the suppliers it sources from which means that a wealth of research is emerging that connects sustainability and purchasing and supply chain management. The textbook provides a comprehensive student guide to the field of Purchasing and Supply Chain Management and the links with environmental sustainability. Although there are a number of supply chain management textbooks available, those which cover sustainability at all do so with "bolt-on" chapters - an approach which fails to integrate the key issues. Aimed at the advanced undergraduate (i.e. year 2 or 3), Masters/MSc, or MBA student, this book integrates theory with practice while drawing on relevant industry case studies"--Resumé vydavatele